Propagation from root cuttings for black locust (Robinia pseudoacacia L.) improvement in Hungary: a review - Keserű, Zs.; Rédei, K.; Rásó, J.; Kiss, T. (International Journal of Horticultural Science, 2019)
Black locust (Robinia pseudoacacia L.) is a valuable stand-forming tree species introduced to Europe approximately 400 years ago from North America. Today it is widely planted throughout the world, first of all for wood production. In Hungary, where black locust has great importance in the forest management, it is mainly propagated by seeds. But since the seed-raised plants present a great genetic variation, this type of propagation can not be used for Robinia’s improved cultivars. In the Hungarian black locust clonal forestry, propagation from root cuttings can be used for reproduction of superior individuals or cultivars in large quantities. However, this method demands more care than raising seedlings from seeds and can be applied with success in well-equipped nurseries.